Pedometer measured physical activity in primary schoolchildren in Kuala Lumpur, Malaysia - Wee, Bee Suan; Awang Bulgiba, Awang Mahmud; Ismail, Mohd Noor; Poh, Bee Koon (2017)
Introduction: Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine-based equation was developed to address the systematic underestimation of the glomerular filtration rate (GFR) by the Modification of Diet in Renal Disease (MDRD) Study equation in patients with a relatively well-preserved kidney function. The objective of this study is to evaluate eGFR by CKD-EPI vs. MDRD equations and to stratify kidney function according to KDIGO guidelines. Method: Serum creatinine from 8754 patients were extracted from our laboratory data. eGFR were calculated using the CKD –EPI and MDRD equations. CKD stages based on two different eGFRs were compared. Results: Sample consisted of 3446 women (40%) and 5308 men (60%). Median age of patient was 58 years and median baseline creatinine was 83mmol/L. Baseline median eGFR was 84.8 and 86.6 mL/min/1.73 m2 for MDRD and CKD-EPI equations (p < 0.001), respectively. Of the 8754 measurements, MDRD classified 2169 (25%) patients as “normal function” (eGFR>90%) while CKD-EPI classified 2720 (31%) patients as “normal function”. 15% patients who were classified as “normal function” with CKD-EPI were classified as “mild reduced GFR” (GFR: 60-89 mL/min/1.73 m2) using MDRD. CKD-EPI classified fewer patients (63%) as eGFR < 60% as compared to MDRD (72%). Conclusion: The CKDEPI equation classified fewer individuals as having reduced kidney function than did the MDRD Study equation across a broad age range.